The Role of Progesterone Induced Blocking Factor in Threatened Abortion - Andre C Widya; Maria F Loho; John J E Wantania (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To determine the role of progesterone-induced blocking factor (PIBF) in women with threatened abortion. Methods: This was a cross-sectional study. The blood serum of two groups, the first one was women with normal gestation of ï‚£ 20 weeks, and the second one was those with imminent abortion in Prof. Dr. R.D. Kandou Hospital, and Subcenter Hospital in Manado, was collected. Samples were processed with PIBF ELISA-kit. Results: PIBF serum value of women in normal gestation ï‚£ 20 weeks is (47.153ï‚±23.830)ng/ml and threatened abortion is (11.540ï‚± 4.892) ng/ml, with p value = 0.000. Conclusion: PIBF serum value of women with threatened abortion is significantly lower compared to women of normal gestation ï‚£ 20 weeks. This study showed that PIBF has an important role in maintaining pregnancy and can be used as a biologic marker of a pathologic process in pregnancy.Keywords: early pregnancy, pregnancy immunology, progesteroneinducedblocking factor, threatened abortion